Analisis Kesehatan Lingkungan Rumah, Penyuluhan dan Pelatihan Pencegahan Tuberkulosis (TB) di Bantul, Yogyakarta - Surahma Asti Mulasari (Jurnal Pengabdian Pada Masyarakat, 2019)
HOME ENVIRONMENTAL HEALTH ANALYSIS, COUNSELING AND TUBERCULOSIS PREVENTION TRAINING (TB) IN BANTUL, YOGYAKARTA. Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, this disease can attack various organs, especially the lungs. This disease, if left untreated or incomplete treatment, can cause dangerous complications to death, and potential to spread to other people. In Hamlet "X" RT 09 Bantul Yogyakarta, there were families with Tuberculosis sufferers. The purpose of this activity was to prevent the risk of TB transmission and increase the knowledge of residents around TB patients at the service location. The method used in this activity was to analyze the condition of the home environment associated with TB, provide training in managing the home environment to be healthy. The impact obtained was an increase in the knowledge of residents and families of TB patients, and reduce the risk of transmission of TB in the home and community environment.